2006
DOI: 10.1126/science.1122692
|View full text |Cite
|
Sign up to set email alerts
|

Oceanographic Basis of the Global Surface Distribution of Prochlorococcus Ecotypes

Abstract: By using data collected during a continuous circumnavigation of the Southern Hemisphere, we observed clear patterns in the population-genetic structure of Prochlorococcus, the most abundant photosynthetic organism on Earth, between and within the three Southern Subtropical Gyres. The same mechanisms that were previously invoked to account for the vertical distribution of ecotypes at local scales accounted for the global (horizontal) patterns we observed. Basin-scale and seasonal variations in the structure and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
167
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(196 citation statements)
references
References 27 publications
27
167
1
1
Order By: Relevance
“…Additionally, six clades denoted by differences in internal transcribed spacer (ITS) sequences displayed distinct distribution patterns on ocean-scale gradients ( Johnson et al 2006). In particular, temperature correlated with occurrence and tolerance limits of different isolates from within the clusters, but other ecological factors also showed a relationship (Bouman et al 2006;Johnson et al 2006). Temperature was also identified as a key regulator in analysis of coexisting Vibrio populations identified as microdiverse 16S rRNA clusters.…”
Section: Sequence Clusters As Populations or Species?mentioning
confidence: 96%
“…Additionally, six clades denoted by differences in internal transcribed spacer (ITS) sequences displayed distinct distribution patterns on ocean-scale gradients ( Johnson et al 2006). In particular, temperature correlated with occurrence and tolerance limits of different isolates from within the clusters, but other ecological factors also showed a relationship (Bouman et al 2006;Johnson et al 2006). Temperature was also identified as a key regulator in analysis of coexisting Vibrio populations identified as microdiverse 16S rRNA clusters.…”
Section: Sequence Clusters As Populations or Species?mentioning
confidence: 96%
“…Thus, like other phytoplankton, the life and death of Prochlorococcus are intimately coupled with that of co-occurring microbes. Although significant advances have been made in understanding 'top down' control of Prochlorococcus populations by phage and grazers (for example, Worden and Binder, 2003;Avrani et al, 2011;Pasulka et al, 2015), as well as 'bottom up' control by nutrients, temperature and light (for example, Bouman et al, 2006;Johnson et al, 2006;Saito et al, 2014), studying how co-occurring heterotrophic microbes affect Prochlorococcus is still in its infancy. Several recent studies have shown that co-occurring heterotrophic bacteria can both enhance and inhibit the growth of Prochlorococcus in laboratory co-cultures (Morris et al, 2008;Sher et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Sampling procedures and nutrient analyses for the ARCTIC, VANC10MV and BEAGLE cruises ( Figure 1 and Table 1) can be found in Not et al (2005Not et al ( , 2008 and Bouman et al (2006). In brief, samples analysed from the Arctic Ocean cruise were collected at six depths from the surface of the water column to B60 m deep in August 2002.…”
Section: Samplingmentioning
confidence: 99%